Novel secoeunicellins produced by an octocoral Cladiella sp. Issue 49 (5th December 2019) - Zhang, Zhi-Jun; Wang, Yi-Hsuan; Chen, Shu-Rong; Peng, Bo-Rong; Yang, San-Nan; Hu, Chiung-Chih; Fang, Lee-Shing; Hwang, Tsong-Long; Sung, Ping-Jyun
Graphical abstract: Highlights: New 6, 7-secoeunicellins, cladieunicellins W (1 ) and X (2 ), were obtained from Cladiella sp. Secoeunicellin 2 displayed significant anti-inflammatory activity. A methoxy group played an important role in determining the activity. Abstract: Two novel 6, 7-secoeunicellins, cladieunicellins W (1 ) and X (2 ), along with a known eunicellin, klymollin Y (3 ), were isolated from an octocoral identified as Cladiella sp. The structures of secoeunicellins 1 and 2 were elucidated by spectroscopic methods. 1 is the first secoeunicellin possessing a γ-lactone ring and 2 represents the first secoeunicellin possessing two tetrahydrofuran moieties. Secoeunicellin 2 displayed significant inhibitory effects on the generation of superoxide anions and the release of elastase. These results implied that the methoxy group at C-6 in 2 plays an important role in determining the activity of these compounds.